2003
DOI: 10.4269/ajtmh.2003.69.6_suppl.0690024
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Human Volunteers With Monovalent and Tetravalent Live-Attenuated Dengue Vaccine Candidates

Abstract: Abstract. Four serotypes of monovalent live attenuated dengue virus vaccine candidates were tested for reactogenicity and immunogenicity in 49 flavivirus non-immune adult human volunteers. The four monovalent candidates were then combined into a tetravalent formulation and given to another 10 volunteers. Neutralizing antibody seroconversion rates after a single-dose monovalent vaccination ranged from 53% to 100%. Solicited reactogenicity was scored by each volunteer. A composite index, the Reactogenicity Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
131
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 31 publications
1
131
0
Order By: Relevance
“…Therefore, we find y 4 oz 2 þ z 4 because 0on 2 À 2n þ 2 for all n 2 R, and conclude that single-serotype vaccinations could potentially increase the number of DHF cases for ADE values associated with an endemic steady-state in the non-vaccination model (before the Hopf bifurcation). We note that single serotype vaccines have been tested in populations with no exposure to dengue and found to have 53-100% seroconversion rates (Sun et al, 2003). No singleserotype vaccines are being evaluated among persons at risk of exposure to dengue nor being designed for routine use because it is assumed that this would have a negative impact on health in any setting.…”
Section: Vaccinationsmentioning
confidence: 99%
“…Therefore, we find y 4 oz 2 þ z 4 because 0on 2 À 2n þ 2 for all n 2 R, and conclude that single-serotype vaccinations could potentially increase the number of DHF cases for ADE values associated with an endemic steady-state in the non-vaccination model (before the Hopf bifurcation). We note that single serotype vaccines have been tested in populations with no exposure to dengue and found to have 53-100% seroconversion rates (Sun et al, 2003). No singleserotype vaccines are being evaluated among persons at risk of exposure to dengue nor being designed for routine use because it is assumed that this would have a negative impact on health in any setting.…”
Section: Vaccinationsmentioning
confidence: 99%
“…An effective DENV vaccine should confer protection for each serotype since all four serotypes commonly circulate in endemic regions, and secondary infection with a heterologous serotype is associated with increased disease severity [9]. Unfortunately, previous attempts to develop a tetravalent, live attenuated vaccine against the DENV have found that one or more vaccine components exhibited either under-or over-attenuation resulting in unacceptable reactogenicity or poor immunogenicity, respectively [10,11]. Modification of the concentration of one of the serotypes in a tetravalent vaccine has not been able to reliably correct problems of reactogenicity or over-attenuation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…7 Given the lack of effective tools for the primary prevention of dengue, there has been a major effort to develop safe and effective dengue vaccines as a tool to prevent this disease. [10][11][12][13][14] Several dengue vaccines are now in late stage development and will begin to move into large scale clinical trials. [15][16][17] Because dengue is endemic in Puerto Rico, it has been considered as a potential site for a dengue vaccine efficacy trial.…”
Section: Introductionmentioning
confidence: 99%